Case report: 177Lu DOTA-TATE: a new scheme for the treatment of prostate neuroendocrine cancer - Yu, Xin-yuan; Zhu, Yu-qin; Liu, Xin; Tian, Rong; Chen, Jun-jie; Liu, Guo-qing; Yang, Dong-yu; Zhang, Xue-ping; Li, Bao; Zhao, Hong-jun; Li, Xiao (Frontiers in Oncology, 2023)
Background Most instances of small cell carcinoma originate from the lungs, while the gastrointestinal tract serves as a secondary site. Only a minuscule proportion of cases manifest within the urogenital system. Prostate small cell carcinoma (SCCP) represents an exceedingly uncommon pathological subtype within the realm of prostate cancer, displaying significant rarity in clinical settings. This scarcity has resulted in a paucity of adequate foundational and clinical research for SCCP treatment. While investigations have unveiled a certain therapeutic efficacy of radiotherapy and chemotherapy for SCCP, clinical practice has revealed suboptimal treatment outcomes. We hereby present a case report detailing the utilization of 177Lu-DOTA-TATE in the treatment of SCCP, aiming to investigate the therapeutic efficacy of 177Lu-DOTA-TATE for SCCP. Case presentation A male patient in his 80s presented with elevated prostate-specific antigen (PSA) levels and underwent a biopsy that revealed prostate adenocarcinoma. The patient received CAB (bicalutamide + goserelin) therapy. One year later, disease progression was detected, and a second biopsy confirmed the presence of prostate small cell carcinoma. Following the diagnosis of prostate small cell carcinoma, the patient underwent two cycles of 177Lu-DOTA-TATE treatment. Subsequent to the treatment, the original lesions showed shrinkage, metastatic lesions disappeared, and there was significant improvement, approaching complete remission. Conclusion SCCP exhibits a high degree of malignancy and aggressive invasiveness, currently lacking effective therapeutic modalities. The treatment course of this patient serves as compelling evidence for the efficacy of 177Lu-DOTA-TATE in managing SCCP, thereby opening new avenues for future SCCP treatments.